Ответ:
2
Пошаговое объяснение:
2^-10 • 2^-12 : 2^-24 • 2^0
(числа равны я нужно просто посчитать корни)
-10 - 12 + 24 + 0 = 2
2^2 = 4
4.
4 ^ (-5) • 16^(-3) : 64^(-4) • 2^0 =
= (2²) ^ (-5) • (2⁴)^(-3) : (2⁶)^(-4) • 1 =
= 2 ^ (-10) • 2^(-12) : 2^(-24) = 2^(-10-12-(-24)) = 2^(-22+24) = 2² = 4.
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
2
Пошаговое объяснение:
2^-10 • 2^-12 : 2^-24 • 2^0
(числа равны я нужно просто посчитать корни)
-10 - 12 + 24 + 0 = 2
2^2 = 4
Ответ:
4.
Пошаговое объяснение:
4 ^ (-5) • 16^(-3) : 64^(-4) • 2^0 =
= (2²) ^ (-5) • (2⁴)^(-3) : (2⁶)^(-4) • 1 =
= 2 ^ (-10) • 2^(-12) : 2^(-24) = 2^(-10-12-(-24)) = 2^(-22+24) = 2² = 4.